Epistemologi Eskatologi dalam Hikmah al-Isyrāq: Rekonstruksi Konsep Jiwa Pasca-Kematian Menurut Suhrawardī al-Maqtūl - Asyraf Malik; Ayu Lestari; Wawan Kurniawan (Paradigma: Jurnal Kalam dan Filsafat, 2025)
Existing studies on Suhrawardī's eschatology have largely focused on the soul and the afterlife, while comparatively little attention has been paid to the epistemological foundation underlying his eschatological thought. This article examines Suhrawardī al-Maqtūl's concept of eschatology by focusing on the relationship between the post-mortem condition of the soul, resurrection, and the epistemological method through which eschatological realities are understood. Employing qualitative library research and textual analysis of Suhrawardī's major works and relevant scholarship on Hikmat al-Ishrāq, the study demonstrates that Suhrawardī classifies the post-mortem condition of the soul into three categories: syaqāwah, su‘adā’ (or zuhhād), and muta’allihīn (or muqaddasīn). These conditions are associated with imaginal forms (al-ṣuwar al-mithāliyyah) that serve as the medium through which the soul manifests in the event of resurrection. The study further argues that Suhrawardī's eschatology is grounded primarily in intuitive (ishrāqī) epistemology rather than demonstrative (burhānī) reasoning, making illuminative knowledge the principal framework for understanding the afterlife. This finding suggests that Suhrawardī's eschatology should be understood not merely as a metaphysical doctrine of the hereafter but as an integral consequence of the epistemological structure of Hikmat al-Ishrāq.